1980
DOI: 10.1177/014544558042002
|View full text |Cite
|
Sign up to set email alerts
|

Social Skills Training for Highly Aggressive Children

Abstract: Four highly aggressive children who were inpatients in a psychiatric hospital were treated with social skills training. Treatment was applied to each child in multiple baseline fashion across behaviors. Results indicated that the treatment was highly effective for each child. However, generalization and maintenance patterns varied substantially across subjects. The results were discussed in regard to the idiosyncratic deficits and treatment needs typically found in clinical populations. The need for individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0
1

Year Published

1983
1983
2003
2003

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…Nonetheless, we note the lack of longterm follow-ups assessing the generalization of the principles learned in the clinical setting to the community. One of the few exceptions is the study by Bornstein, Bellack, and Hersen (1980), a multiple-baseline study of four aggressive hospitalized adolescent inpatients, The authors reported a decrease in aggressiveness six months after treatment.…”
Section: Violent Offendersmentioning
confidence: 99%
“…Nonetheless, we note the lack of longterm follow-ups assessing the generalization of the principles learned in the clinical setting to the community. One of the few exceptions is the study by Bornstein, Bellack, and Hersen (1980), a multiple-baseline study of four aggressive hospitalized adolescent inpatients, The authors reported a decrease in aggressiveness six months after treatment.…”
Section: Violent Offendersmentioning
confidence: 99%
“…En relación a los trastornos del comportamiento perturbador, también encontramos referencias (Hawkins, Catalano, y Morrison, 1989;Kendall, 1991;Pepler y Rubin, 1991;Arnold y Forehand, 1978;Michelson, Sugai, Wood y Kazdin, 1983;Dodge y Frame, 1982;Ladd,1981;Bornstein y Bellack, 1980). Es importante recordar la estrecha relación entre conducta antisocial y abuso en el consumo de alcohol y drogas (Kellam y Brown, 1982).…”
unclassified
“…More recently, researchers have focused on cognitive aspects of anger control problems, and multi-component programs including both behavioral and cognitive techniques have become the treatment approach of choice (McMahon & Wells, 1998). Social skills training for this purpose has incorporated procedures such as modeling (e.g., Bornstein, Bellak, & Hersen, 1980), problem-solving (Cavell & Hughes, 2000;Kazdin, Siegel & Bass, 1992;Spivack & Shure, 1974), self-instruction (Dangel, Deschner, & Rasp, 1989;Larson, 1992;Lochman & Curry, 1986), and home-based reinforcement (Barkley, 1989;McCain & Kelley, 1993).…”
mentioning
confidence: 99%
“…Limitations in previous research on the treatment of anger control problems in children include a lack of significant results or minimal positive change (Cavell & Hughes, 2000;Dangel et al, 1989;Larson, 1992;Lochman & Curry, 1986), decreases in negative behaviors without corresponding increases in positive behaviors (Clark et al, 1973), and failure to generalize to other settings (Bornstein et al, 1980). While the treatment approaches described above have not always been successful, it has been suggested that they are more effective when used in combination (McMahon & Wells, 1998).…”
mentioning
confidence: 99%